Bio‐polymer modified nanoclay embedded forward osmosis membranes with enhanced desalination performance. Issue 27 (29th April 2022) - Mamah, Stanley Chinedu; Goh, Pei Sean; Ismail, Ahmad Fauzi; Yogarathinam, Lukka Thuyavan; Suzaimi, Nur Diyana; Opia, Anthony Chukwunonso; Ojo, Samuel; Ngwana, Ngouangna Eugene
Abstract: The substrate of forward osmosis (FO) thin‐film composite (TFC) membranes supports the formation of the selective layer. It can remarkably influence the structure as well as the physiochemical characteristics of the selective layer formed atop. Therefore, the improvement of TFC substrates in terms of its thickness, tortuosity and porosity can further fine tune the properties of the resultant TFC membranes. In this present study, TFC membrane comprising of polyamide selective layer and palygorskite‐chitin (PAL‐CH) containing polysulfone substrate was developed for FO desalination. The effects of PAL‐CH on the surface and structural properties of the substrate were examined. The FO desalination performance of the resultant membranes was evaluated in both active‐layer facing feed solution and active‐layer facing draw solution modes using NaCl as draw solution. In comparison with the un‐modified membrane, the TFC membrane with PAL‐CH embedded polysulfone substrate exhibited enhanced water flux and lower structural parameter. The incorporation of PAL‐CH hybrid nanomaterial resulted in improved flux of 34.39 L/m 2  h 1, which corresponds to improvement by 110% compared to that of pristine membranes. During the antifouling test, PAL‐CH‐S/PA membrane attained 97% water recovery while the pristine membrane attained 90% water recovery. Abstract :